Effect of aldosterone on the amplification of oncolytic vaccinia virus in human cancer lines - Lee, Hyun Ju; Rho, Jasung; Gui, Shao Ran; Kim, Mi Kyung; Lee, Yu Kyoung; Lee, Yeon Sook; Kim, Jeong Eun; Cho, Euna; Cho, Mong; Hwang, Tae-Ho (Clinical and molecular hepatology, 2011)
JX-594 is an oncolytic virus derived from the Wyeth vaccinia strain that causes replication-dependent cytolysis and antitumor immunity. Starting with a cross-examination of clinical-trial samples from advanced hepatocellular carcinoma patients having high levels of aldosterone and virus amplification in JX-594 treatment, we investigated the association between virus amplification and aldosterone in human cancer cell lines. Cell proliferation was determined by a cell-counting-kit-based colorimetric assay, and vaccinia virus quantitation was performed by quantitative polymerase chain reaction (qPCR) and a viral plaque assay. Also, the intracellular pH was measured using a pH-sensitive dye. Simultaneous treatment with JX-594 and aldosterone significantly increased viral replication in A2780, PC-3, and HepG2 cell lines, but not in U2OS cell lines. Furthermore, the aldosterone treatment time altered the JX-594 replication according to the cell line. The JX-594 replication peaked after 48 and 24 hours of treatment in PC-3 and HepG2 cells, respectively. qPCR showed that JX-594 entry across the plasma membrane was increased, however, the changes are not significant by the treatment. This was inhibited by treatment with spironolactone (an aldosterone-receptor inhibitor). JX-594 entry was significantly decreased by treatment with EIPA [5-(N-ethyl-N-isopropyl)amiloride; a Na(+)/H(+)-exchange inhibitor], but aldosterone significantly restored JX-594 entry even in the presence of EIPA. Intracellular alkalization was observed after aldosterone treatment but was acidified by EIPA treatment. Aldosterone stimulates JX-594 amplification via increased virus entry by affecting the H(+) gradient.